2014
DOI: 10.1108/ccij-09-2012-0066
|View full text |Cite
|
Sign up to set email alerts
|

Organizational blogging: a case study of a corporate weblog from an employee perspective

Abstract: Purpose – The aim of this paper is to address and discuss usage and implications of a weblog in a corporate communication context from an employees' perspective. Design/methodology/approach – The paper is a case study of a government agency's corporate blogging activity, traced through focus group interviews with the organizational bloggers and analyzed using situational analysis and thematic network analysis. Findings – The study problematizes the predominant focus on the promises of interactivity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…Another factor likely to influence coworker communication on ISM is the variety of user-types in online communities (Agerdal-Hjermind, 2014; Brandtzaeg and Heim, 2011; Li and Bernoff, 2011). The study most relevant to ISM is Brandtzaeg and Heim’s (2011) study of four closed Norwegian social networks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another factor likely to influence coworker communication on ISM is the variety of user-types in online communities (Agerdal-Hjermind, 2014; Brandtzaeg and Heim, 2011; Li and Bernoff, 2011). The study most relevant to ISM is Brandtzaeg and Heim’s (2011) study of four closed Norwegian social networks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This has brought out our concern about how an organization's communication platform, in particular when incorporating social media, can relate to communicational ambidexterity. The second area emphasizes different managerial issues and challenges related to the use of social media, such as protection of intellectual property (Väyrynen, et al, 2013), security and privacy (Andriole, 2010) and employee motivation (Agerdal-Hjermind, 2014). A growing number of papers have pointed out that social media can be a double-edge sword.…”
Section: About Here>mentioning
confidence: 99%
“…Previous research also show how motivations in social media use differ between employees. Agerdal‐Hjermind () highlighted the subjective and multifaceted nature of internal blogging within a government office, identifying four categories of bloggers: the official, the debater, the engineer, and the passionate. Similarly, in terms of information sharing, DiMicco et al () identified three strategies—caring, climbing, and campaigning—used by the employees in a social networking site.…”
Section: Introductionmentioning
confidence: 99%